Rebuilding Tourism Competitiveness : Tourism Response, Recovery and Resilience to the COVID-19 Crisis - World Bank (World Bank, Washington, DC, 2020)
The travel and tourism industry was one of the first sectors to be affected by COVID-19. Since March, the entire value chain that defines the industry — spanning airlines, bus and train companies, cruise lines, hotels, restaurants, attractions, travel agencies, tour operators,online travel entities, and others — has entered a state of suspended animation. While bankruptcies of major airlines and large tour operators have been widely reported, the effectsof the crisis are perhaps being most acutely felt by the Small and Medium-sized Enterprises(SMEs) that make up around 80 percent of licensed tourism and tourism-related businesses, and are at the greatest risk of failure. Their potential collapse threatens to adversely affect millions of people across the world, including many vulnerable communities, who depend on tourism for their livelihoods. According to the World Travel and Tourism Council, as many as 100 million jobs supported by travel and tourism are currently at risk.